Prevalence of stroke and transient ischemic attack in Takayasu’s arteritis : a systematic review - Samartinho, Marta Maria Duarte (2017)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2015